Investigation on the effect of press temperature and time on physical and mechanical properties corn stalk MDF - Abolfazl Karegarfard (Regional Information Center for Science and Technology (RICeST), 2013)
The objective of this investigation was the utilization of corn stalk in Medium Density Fiberboard (MDF) production. Therefore 27 laboratory MDF boards were produced using three press temperatures of 165, 175 and 185 °C and three press duration of 3, 3.5 and 4 minutes. The mechanical and physical properties of the boards were measured and the results were statistically analyzed. The results indicated that press temperatures and press duration did not impose significant effect on MOR, but with increasing the press temperature and press duration, the MOE of the boards improved and the highest MOE was observed applying 185 °C press temperatures and 4 minutes press duration. The internal bonding (IB) of boards increased with increasing press duration, and the highest IB was related to boards produced with 3.5 and 4 minutes press duration. The press duration significantly influenced the thickness swelling after 2 and 24 hours immersion in water, and the lowest values were observed in boards produced applying 3.5 minutes press duration, as expected from the results of highest IB at same condition. Generally it can be expressed that corn stalk shows the potential as raw material to produce standard Medium Density Fiberboard.